Psychrophiles : from biodiversity to biotechnology - Margesin, Rosa, 1962- (Springer, 2017)
This completely updated and revised second edition presents the most recent developments and advances in the field of microbial life in the cold, as well as the latest insights into the psychrophilic lifestyle. It particularly focuses on the exploitation of psychrophiles as a source of cold-active enzymes and biopolymers, and their benefits in the fields of biomedicine and bioremediation. Written by leading international experts, the book is intended for microbiologists, ecologists, molecular biologists, biochemists, environmental scientists and biotechnologists in academia and industry.
Keywords: Extreme environments -- Microbiology.; elektronické knihy; electronic books